DIAGNOSIS OF BONE BY ULTRASONIC WAVE - OTANI TAKAHIKO; HOSOKAWA ATSUSHI; HIRATA HARUYOSHI; SUZAKI TAKUJI (1997)
PROBLEM TO BE SOLVED: To facilitate determination of bone characteristics such as bone quantity and bone strength by radiating ultrasonic waves outputted from an ultrasonic transmitting part to a human bone to be transmitted, receiving the transmitted waves by an ultrasonic receiving part, and comparing an obtained diagnosis waveform with a reference waveform. SOLUTION: In making diagnosis of a bone, a forearm 8 is inserted between an ultrasonic transmitting part 2 and an ultrasonic receiving part 4, and a subject part of the fore arm 8 is tightly applied to sound impedance matching bodies 10 respectively provided on fore arm abutting part of the ultrasonic transmitting part 2 and the receiving part 4. In this condition, ultrasonic pulse waves S of a frequency of 5MHz or less, for example, are transmitted from the ultrasonic transmitting part 2 to be transmitted through a soft organization 9 through a flexible bone 3 to be received by the ultrasonic receiving part 4. A received transmitting wave signal is taken through a signal amplifier 5 into a computer 6, its diagnosis waveform is compared with a reference waveform, a condition of the human bone is diagnozed, and result of it is displayed in a display device 7.